Antecedents of happiness at work: The moderating role of gender - Moyassar Al-Taie (Cogent Business & Management, 2023)
AbstractHappiness at the workplace (HAW) has received growing scrutiny in the last two decades. However, little is known about the factors that determine this central organizational phenomenon. This study investigates the relationship between three organizational factors (high commitment human resources practices (HCHRPs); perceived organizational support (POS); and organizational respect for non-work (ORN)) and three personal factors (passion for work (PFW), employee psychological capital (PsyCap), and gender), and HAW as a holistic and multidimensional construct. Data obtained from 359 university professors in the United Arab Emirates was analyzed using a (PLS/SEM) to test the research hypothesis. Findings indicate that POS, HCHRPs, PFW, and PsyCap have a significant positive relationship with HAW. However, no significant relationship between ORN and HAW was found. A PLS multi-group analysis indicated that gender was not found to ameliorate these relationships. Implications of the findings, limitations and future research are discussed.